Diagnostic difficulty of an aggressive and recurrent giant cell granuloma: a short case report - De Cidrac Louis; Kadri Mohamed; Pecorari Roch; Nguyen Thông; Radoï Loredana (EDP Sciences, 2021)
Introduction: The central giant cell granuloma (CGCG) is a rare benign lesion of the jaws, rarely aggressive,mostly affecting the mandible in children and young adults. The diagnosis may be difficult, complementaryhistological analyses being necessary to differentiate it from other giant cell tumours. Observation: A 28-year-old woman consulted for a painful gingival swelling surrounding the inferior right second molar. Cone Beam (CBCT) showed anunilocular radiolucent mandibular lesion. Histological examination performed after the curettage of the lesion could not differentiate between a peripheral GCG with bone extension, a giant cell tumour (GCT) or a CGCG. The patient was lost of view for 4 months until an aggressive recurrence. Asegmental mandibulectomy in disease-free margin was performed. Immunohistochemical and genetic testscomplementary to histology finally permitted to concludeto a CGCG. The patient presented no recurrence in 4 years of follow-up. Discussion: Surgical removal in disease-free margin is the gold standard treatment in aggressive CGCG. Nonetheless, literature reports alternative pharmacological treatments alone or in addition to surgery. In this case, the aggressiveness of the tumour and the absence of patient compliance for follow-up have led to the decision of a radical treatment of the recurrence. Conclusion: Aggressive CGCG requires a rapid diagnosis and a primary disease-free margin surgical resection to avoid mutilating treatment of the recurrence.